Boko Haram Terrorism and a Threat to Right to Education - Ayobami Samson Joshua (Faculty of Law, Hasanuddin University, 2020)
The government shall direct its policy towards giving to the citizens equal and adequate educational opportunities at all levels. Although, not classified as a fundamental right, this constitutional prescription remains at the forefront of the basic objectives of the Nigerian government; yet, despite this laudable objective, the Northern region of Nigeria has a consistent record of low enrolment rate of indigenous pupils in schools, thereby creating a noticeable disparity between the North and South of Nigeria in terms of education. It is against this background that this paper discusses the evolution, incidences and enabling circumstances of Boko Haram terrorism in Nigeria and its effects on education, particularly in the areas affected. The purpose of this paper is to discuss the long term consequences of the Boko Haram terrorism on the right to education, as guaranteed by the 1999 constitution, in the affected areas of Nigeria. The paper traces the origin and factors that aided the Boko Haram terrorism. It also considers the extent of the effectiveness of the response of the Nigerian government in tackling the problem. The findings prove that, although the response of the government has been active, yet it has not been effective in curtailing the terrorist activities. This has negatively impacted on education in the affected areas of the Northern Nigeria. The paper suggested measures to address the problem.